PENGARUH DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN ON EQUITY PADA PT UNILEVER INDONESIA TBK PERIODE 2013-2022 - Ramadhan, Fitroh; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Debt to Equity Ratio and Net Profit Margin on Return On Equity at PT Unilever Indonesia Tbk. Period 2013-2022. The method used in this research is kuantitative descriptive with data retrieval techniques using secondary data and sampling techniques using purposive sampling in the form of financial position reports and income statements and data analysis techniques used are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, coefficient test, and hypothesis testing through the Statistical Product and Service Solution27 program. The results of this study indicate that: Partially Debt to Equity Ratio has a significant effect on Return On Equity with a t-count value of 3.018> t-table 2.365 and a sig value. Net Profit Margin has no effect and is not significant with a t-count value of 1.337 < t-table 2.365 and a sig value. Simultaneously Debt to Equity Ratio and Net Profit Margin have a significant effect on Return On Equity with an f-count value of 5.982> f-table 4.74 and a sig value. 0.031 <0.05. And it can be seen in the coefficient of determination that the Adjusted R Square value is 0.525 or 52,5%, meaning that the Debt to Equity Ratio and Net Profit Margin variables together contribute to the Return On Equity. Variable by 52,5% while the remaining 47,5% is heard.